NO Promotes Seed Germination and Seedling Growth Under High Salt May Depend on EIN3 Protein in Arabidopsis - Li, Xilong; Pan, Yajie; Chang, Bowen; Wang, Yucheng; Tang, Zhonghua (Frontiers in Plant Science, 2016)
The gas molecule NO can cooperate with ethylene to tightly modulate plant growth and stress responses. One of the mechanism of their crosstalk is that NO is able to activate ethylene biosynthesis, possibly through post-translational modification of key enzymes such as ACC synthase and oxidase by S-nitrosylation. In this paper, we focus on the crosstalk of NO with ethylene signaling transduction transcription factor EIN3 (Ethylene Insensitive 3) and downstream gene expression in alleviating germination inhibition and growth damage induced by high salt. The Arabidopsis lines affected in ethylene signaling (ein3eil1) and NO biosynthesis (nia1nia2) were employed to compare with the wild-type Col-0 and overexpressing line EIN3ox. Firstly, the obviously inhibited germination, greater ratio of bleached leaves and enhanced electrolyte leakage were found in ein3eil1 and nia1nia2 lines than in Col-0 plants upon high salinity. However, the line EIN3ox obtained a notably elevated ability to germinate and improved seedling resistance. The experiment with SNP alone or plus high salt mostly enhanced the expression of EIN3 transcripts, compared with ACO4 and ACS2. The western blot and transcript analysis found that high-salt-induced EIN3 stabilization and EIN3 transcripts were largely attenuated in the NO biogenesis mutant nia1nia2 plants than in Col-0 ones. This observation was confirmed by simulation experiments with NO scavenger cPTIO to block NO emission. Taken together, our study provides insights that NO promotes seed germination and seedlings growth under salinity may depend on EIN3 protein.